THE HEAT CAPACITY OF SYNTHETIC ANHYDROUS MG AND FE CORDIERITE - Geiger C.A.; Voigtlander H. (My University, 2000)
The heat capacity of synthetic anhydrous Mg and Fe cordierite was measured by differential scanning calorimetry (DSC). Mg cordierite was synthesized from a glass at high temperatures and shows an ordered structural state. Fe cordierite was synthesized hydrothermally and dehydrated under reducing conditions to obtain H2O-free material. IR spectroscopy was used to ascertain the lack of H2O in both phases. The molar volume of both phases was measured using powder X-ray diffraction giving 23.316 (7) J/bar for Mg cordierite and 23.672 (6) J/bar for Fe cordierite. DSC measurements between 300 and 950 K were made following the procedure of Bosenick et.al. (1996). The data show a precision of about 1% in the case of Mg cordierite and 1.5% for Fe cordierite. Fitted Cp polynomials in J/mol/K are: and for Mg and Fe cordierite, respectively. The Cp values determined for Mg cordierite are slightly larger (1–3%) than those measured by drop calorimetry by Pankratz and Kelley (1963). The Cp data for Fe cordierite permit the calculation of its standard third-law entropy, So 298 K from the reaction 3Fe cordierite=2 almandine + 4 sillimanite + 5 quartz giving 465 J/mol/K, which is in good agreement with recent model estimates.